Between views - Augaitis, Daina; Gilbert, Sylvie; Walter Phillips Gallery, The Banff Centre School of Fine Arts, Banff (Banff : Walter Phillips Gallery - The Banff Centre for the Arts Banff, 1991)
Steinman, Barbara ; Magor, Liz ; Morgan, Joey : Decostere, Stefaan ; Belmore, Rebecca ; Yoon, Jin-Me ; Hock, Louis ; Sisco, Elizabeth
Between Views and Points of View, a series of six porjects commissioned by the Walter Phillips Gallery, Banff, which took place from June to September, 1991
boek